Problems of waqf administration and proposals : a study in Malaysia - Mohd Zulkifli Muhammad; Md. Shahedur Rahaman Chowdhury; Iftekhar Amin Chowdhury (2012)
The main purpose of this paper is to assess the performance of the existing Waqf administration in Malaysia. This paper first describes the problems of Waqf administration in Malaysia and then suggests proposals for improvement. Waqf administration requires new innovative avenues. It also needs to develop a hybrid viable model for generating more benefits for all involving parties of the society with sustainability characteristics. It is recognized that there is no ample study in the area of Waqf. Further, literature is very scanty relating to the Waqf administration. The exiting studies identify various facets of the Waqf and its administration issue to explore different aspects of theoretical dimensions and practices.